STANDARDIZING THE SELECTION OF SEASONAL-PUMPED STORAGE PROJECTS - Hunt, Julian D.; Freitas, Marcos Aurélio Vasconcelos de (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Brazil has just came out of a severe energy crisis and several regional water crisis, which started in 2013 and lasted until the end of 2015. The electricity supply and demand imbalance will further deteriorate with the operation of new dams in the Amazon that will generate most of their energy during the wet period. Seasonal-Pumped-Storage (SPS) is a solution to increase energy storage in a seasonal fashion. SPS stores potential energy during the wet season, when there is excess flow in the river, or when there is excess energy in the grid, pumping water to an upper reservoir. During the dry season, or when there is lack of flow in the river, or when there is lack of energy in the grid, the stored water generates electricity in the SPS and in the dams in cascade. This paper implements an integrated tool and decision support framework to approach complex, long-term problems involving the selection of Seasonal-Pumped Storage projects. The framework is embedded in an integrated tool called OUTDO (Oxford University Tool for Decision Organization). This analysis shows that the South region of Brazil should be selected region to build the first SPS project in Brazil.